Water-soluble anion exchange material
The development of a stable water-insoluble anion exchanger material with improved alkali and temperature resistance addresses the limitations of existing materials, enhancing performance and expanding application possibilities in anion exchange membranes and resins.
Patent Information
- Application Number
- JP2022200406
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-04-27
- Filing Date
- 2022-12-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2037-04-26
AI Technical Summary
Existing anion exchange materials lack sufficient stability in water and alkali environments, especially at temperatures above 50°C, limiting their application in electrochemical treatments and energy systems.
A water-insoluble anion exchanger material composed of linearly polymerized, branched, and crosslinked anion exchange groups connected to a water-insoluble polymer via chemical or ionic bonds, with specific structural units and terminal groups ensuring temperature and alkali stability.
The material exhibits enhanced stability in alkaline conditions and high temperatures, enabling improved performance in anion exchange membranes and resins, opening new application areas and enhancing efficiency in existing applications.
Smart Images

Figure 0007611888000001 
Figure 0007611888000002 
Figure 0007611888000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of polymer chemistry and to water-insoluble anion exchanger materials which can be used, for example, for anion exchange membranes or as anion exchange resins for water treatment (in catalysis), for electrochemical processes (electrodialysis or electrodeionization) or in energy converter systems (e.g. fuel cells and reverse electrodialysis) or in energy storage systems (e.g. redox flow batteries). [Background technology]
[0002] A large number of anion exchange materials are known.
[0003] Known anion exchange resins consist, for example, of cross-linked polystyrene having benzyltrimethylammonium groups as functional groups. For the use of such anion exchange resins in the OH form, operating temperatures of 35° C. up to a maximum of 60° C. are described (data sheet Amberjet 9000 OH; data sheet DOWEX Marathon A; data sheet DOWEC Marathon 2; Dow Chemical Company).
[0004] The thermal stability of various low molecular weight quaternary ammonium salts at 160 °C in 6N NaOH was investigated by Marino and Kreuer (ChemSusChem8, 2015, 513-523), where the spirocyclic compound azoniaspiro[5.5]undecane was found to exhibit the highest stability under the conditions tested.
[0005] Aromatic anion-exchange membranes based on polyethersulfones bearing N-spirocyclic ammonium groups are known from Pham and Jannasch, ACS Macro Letters 4 (2015) 1370-1375, where the spirocyclic anion-exchange groups are condensed to phenyl rings and also bear benzylic methylene groups.
[0006] Investigation of the stability of these anion exchange membranes in 1 M sodium hydroxide solution showed partial decomposition already after 168 h at 40°C.
[0007] According to Hellwinkel and Seifert, bis-2,2'-biphenylene ammonium iodide exhibits high thermal stability at its boiling point in alkaline media (e.g., 20% sodium hydroxide solution). However, the synthesis of this compound is very costly, so its use as a material for anion exchange membranes is not economically viable (Liebigs Ann. Chem. 762 (1972) 29-54).
[0008] Copolymers of chlorotrifluoroethylene and diallyldimethylammonium chloride have been described as binder materials for alkaline fuel cells by Valade et al. (J. Polym. Sci.: Part A: Polym. Chem. 47, 2009, 2043-2205).
[0009] A drawback with this compound is that its low ion exchange capacity precludes its use as a membrane material.
[0010] An anion exchange membrane based on a blend of poly(diallyldimethylammonium chloride) and polyvinyl alcohol is known by Qiao et al. (J. Power Sources 237, 2013, 1-4). To reduce water absorption, the material is crosslinked with glutaraldehyde. The ion exchange capacity of this membrane was stable in 8N potassium hydroxide solution for 375 h after an initial capacity loss of 55%.
[0011] The polymerization and structure of N,N-diallylpyrrolidinium bromide are known from Vynck et al. (Macromol. Rapid Commun. 18, 1997, 149-156).
[0012] A drawback of the known solutions for anion exchanger materials is that these materials are still not sufficiently stable with regard to their water insolubility, especially at temperatures above 50° C. in alkaline environments. [Prior art documents] [Non-patent literature]
[0013] [Non-Patent Document 1] Marino and Kreuer, ChemSusChem8, 2015, 513-523) [Non-Patent Document 2] Pham and Jannasch, ACS Macro Letters 4 (2015) 1370~1375 [Non-Patent Document 3] Hellwinkel and Seifert, Liebigs Ann. Chem. 762 (1972) 29-54 [Non-Patent Document 4] Valade et al., J.Polym.Sci.:Part A:Polym.Chem.47, 2009, 2043~2205 [Non-Patent Document 5] J.Power Sources 237, 2013, 1~4 [Non-Patent Document 6] Vynck et al., Macromol. Rapid Commun. 18, 1997, 149-156 Summary of the Invention [Problem to be solved by the invention]
[0014] It is an object of the present invention to provide a water-insoluble anion exchanger material which exhibits improved alkaline and temperature stability as well as improved water insolubility, especially at temperatures above 50°C. [Means for solving the problem]
[0015] This problem is solved by the invention as set forth in the claims. Advantageous embodiments are the subject of the independent claims.
[0016] The water-insoluble anion exchange material comprises at least anion exchange groups C which are linearly polymerized and / or branched and / or crosslinked with each other, said anion exchange groups C being represented by the following general formulae I to VIII: [ka] [ka] (however, R1 is nitrogen and / or phosphorus, R2 to R9 are substituents, where R2 and R3 are hydrogen or, if at least one of the groups R2 and R3 is not hydrogen, R2 and / or R3 are alkyl or aryl groups; R4 and R5 are each an alkyl group and / or an aryl group; R6 to R9 are hydrogen or, if at least one of the groups R6 to R9 is not hydrogen, then these groups R6 to R9 are alkyl or aryl groups; Z is a terminal group, X is a bond, ·V is a bridge part, K is an end group Z or a bond X, D is absent or at least one methylene group or oxygen or sulfur; B is a water-insoluble polymer that exhibits temperature and alkali stability, A is a non-functional comonomer, 2≦n≦100, m=0 or 1, 1≦o≦100, 50 mol%≦x≦99 mol%, and y=(100 mol%−x), 10 mol%≦w≦100 mol%, and (n+w)=100 mol%) A structural unit component consisting of at least one of the following: Where: In the case of K, there is at least one end group Z and at least one bond X, an anion exchange group C is connected to a water-insoluble polymer B via one or more or all of the bonds X as a constituent of a structural unit according to the general formulae I to IV, and substantially all of the end groups Z are compounds that exhibit temperature stability and alkali stability; and / or anion exchange groups C are crosslinked to each other via crosslinking moieties V as structural unit components of general formulae V to VIII, substantially all end groups Z are compounds exhibiting temperature stability and alkali stability, and all K, which are bonding moieties X, are connected to the water-insoluble polymer B by chemical covalent bonds; and / or The anion exchange group C and the water-insoluble polymer B are connected by one or more ionic bonds.
[0017] Advantageously, at least two anion exchange groups C according to formulae I to IV are interconnected with the water-insoluble polymer B by chemical covalent bonds via the linkage X, and / or the anion exchange groups C are connected with the water-insoluble polymer B by ionic bonds, and the terminal group Z is a compound that exhibits temperature and alkali stability.
[0018] More preferably, the bond X is N,N-diallylpiperidinium ether, or N,N-diallylpyrrolidinium ether, or N,N-diallylaminoethyl ether, or methacrylamide ethyl ether, or methacrylic acid ester, or methacrylic acid hydroxypropyl ether, or xylylene ether, or phenylene ether sulfone.
[0019] Also advantageously, the anion-exchange groups C according to formulae V-VIII are bridged via a bridge V and K is a linking moiety X to which the water-insoluble polymer B is attached by a chemical covalent bond.
[0020] A further preferred embodiment is where the water-insoluble polymer B is connected to the anion-exchange group C according to the general formulae I-VIII by an ionic bond.
[0021] Also advantageously, the terminal group Z is an alkyl thioether or an aryl thioether or a benzyl thioether.
[0022] It is also advantageous if the temperature- and alkali-stable water-insoluble polymer B is a polyethersulfone, or a polythioethersulfone, or a polysulfone, or a polyphenylene, or a polyphenylene ether, or a polyphenylene sulfide, or a poly(perfluoroethylene propylene), or a polytetrafluoroethylene, or a poly(ethylene-tetrafluoroethylene), or a perfluoroalkoxy polymer, or a polystyrene, or a polyethylene, or a polypropylene, or a sulfonated and / or carboxylated and / or phosphonated polymer from the classes of polyethersulfone, or a polysulfone, or a polyphenylene, or a polyphenylene ether, or a polyphenylene sulfide, or a poly(perfluoroethylene propylene), or a polytetrafluoroethylene, or a poly(ethylene-tetrafluoroethylene), or a perfluoroalkoxy polymer, or a polystyrene, or a polyethylene, or a polypropylene.
[0023] It is also advantageous if the comonomer A is styrene, and / or α-methylstyrene, and / or N-vinylcarbazole, and / or methacrylic esters, and / or N-vinylpyrrolidone, and / or N,N-diallylacrylamide, and / or N,N-diallylacrylsulfonamide, and / or diallyl ethers, and / or 1,2-diallylbenzene, and / or diallyl sulfides, and / or chlorotrifluoroethylene, and / or tetrafluoroethylene, and / or hexafluoropropylene, and / or 1,2-divinylbenzene.
[0024] the crosslinking portion V is tetraallyl ammonium chloride, or tetraalkylallyl ammonium chloride, or diallyl-dialkylallyl ammonium chloride, or 1,4-divinylbenzene, or divinyl sulfone, or divinyl sulfide, or divinyl sulfoxide, or divinyl ether, or diacrylamide, or dimethacrylamide, or N,N,N',N'-tetraallyl-4,4'-trimethylenedipiperidinium chloride, or N,N,N',N'-tetraalkylallyl-4,4'-trimethylenedipiperidinium chloride, or N,N-diallyl-,N',N'-dialkylallyl-4,4'-trimethylenedipiperidinium chloride, or N-allyl-N ,N',N'-trialkylallyl-4,4'-trimethylenedipiperidinium chloride, or N,N,N'-triallyl-N'-alkylallyl-4,4'-trimethylenedipiperidinium chloride, or N,N,N',N'-tetraallylpiperazinium chloride, or N,N,N',N'-tetraalkylallylpiperazinium chloride, or N,N-diallyl-N',N'-dialkylallylpiperazinium chloride, or N-allyl-N,N',N'-trialkylallylpiperazinium chloride, or N,N,N'-triallyl-N'-alkylallylpiperazinium chloride, and / or the bromides and / or iodides of these compounds.
[0025] As monomers for producing the anion exchange group C, N,N-diallyl compounds of aliphatic, aromatic or alicyclic secondary amines and / or N,N-dialkylallyl compounds and / or N-allyl-N-alkylallyl compounds are used, such as diallyldimethylammonium chloride, diallylpiperidinium chloride, diallylpyrrolidinium chloride, allyl-methallyldimethylammonium chloride, allyl-methallylpiperidinium chloride, allyl-methallylpyrrolidinium chloride, dimethallyldimethylammonium chloride, dimethallylpiperidinium chloride, dimethylallylpyrrolidinium chloride, diallyl-3,4-dimethyl It is further advantageous if P,P-diallyl compounds of aliphatic or aromatic or cycloaliphatic secondary phosphines, and / or P,P-dialkylallyl compounds, and / or P-allyl-P-alkylallyl compounds, such as, for example, diallyldimethylphosphonium chloride, diallyldiphenylphosphonium chloride, and / or the bromides and / or iodides of these compounds, are used.
[0026] It is also advantageous if R1 is nitrogen.
[0027] It is also advantageous if R2 and / or R3 are methyl groups and / or hydrogen.
[0028] It is likewise advantageous if R4 and R5 are alkyl groups, preferably methyl or ethyl groups.
[0029] It is further advantageous if R6 to R9 are hydrogen.
[0030] It is also advantageous if 10≦n≦50.
[0031] It is also advantageous if 2≦o≦10.
[0032] The present invention makes it possible for the first time to describe water-insoluble materials for anion exchange membranes which have improved alkaline and temperature stability, especially at temperatures above 50°C.
[0033] This is achieved by a water-insoluble anion exchanger material consisting of at least linearly polymerized and / or branched and / or cross-linked anion exchange groups C, which have the following general formulae I to VIII: [ka] [ka] (however, R1 is nitrogen and / or phosphorus, R2 to R9 are substituents, where R2 and R3 are hydrogen or, if at least one of the groups R2 and R3 is not hydrogen, R2 and / or R3 are alkyl or aryl groups; R4 and R5 are each an alkyl group and / or an aryl group; R6 to R9 are hydrogen or, if at least one of the groups R6 to R9 is not hydrogen, then these groups R6 to R9 are alkyl or aryl groups; Z is a terminal group, X is a bond, ·V is a bridge part, K is an end group Z or a bond X, D is absent or at least one methylene group or oxygen or sulfur; B is a water-insoluble polymer, A is a non-functional comonomer, 2≦n≦100, m=0 or 1, 1≦o≦100, 50 mol%≦x≦99 mol%, and y=(100 mol%−x), 10 mol%≦w≦100 mol%, and (n+w)=100 mol%) It is a component of a structural unit consisting of at least one of the following:
[0034] According to the present invention, In the case of K, there is at least one end group Z and at least one bond X, an anion exchange group C is connected to a water-insoluble polymer B via one or more or all of the bonds X as a constituent of a structural unit according to the general formulae I to IV, and substantially all of the end groups Z are compounds that exhibit temperature stability and alkali stability; and / or anion exchange groups C are crosslinked to each other via crosslinking moieties V as structural unit components of general formulae V to VIII, substantially all end groups Z are compounds exhibiting temperature stability and alkali stability, and all K, which are bonding moieties X, are connected to the water-insoluble polymer B by chemical covalent bonds; and / or The anion exchange group C and the water-insoluble polymer B are connected by one or more ionic bonds.
[0035] Thus, the water-insoluble anion exchange material according to the invention has a linear polymerized and / or branched and / or crosslinked structure.
[0036] Here, the anion-exchange groups C can be present only in a linearly polymerized state and / or in a branched state and / or in a three-dimensionally crosslinked state with each other and / or with the compound. This means that when only structural units according to the general formulae I to IV are present, these structural units can only be present in a linearly chemically and / or branched form. The branched compounds of the anion-exchange groups are preferably linearly polymerized compounds with side chains that are present in a substantially chemically unlinked state with each other.
[0037] When structural units according to the general formulae V to VIII are present, linear portions of the structural units, which may also be branched, are also present depending on the length of the structural units used, but at the crosslinking points the structural units according to the general formulae V to VIII are always chemically connected in three dimensions and thus crosslinked.
[0038] The structural units according to the general formulae I to VIII are necessarily linked to a water-insoluble polymer B, preferably aromatic or aliphatic, which is inert under the conditions of use, in which the anion-exchange group C is linked at least at the end of the polymer B via a linkage X and / or K (if K is X). The other end of the polymer chain forms an end group Z or K, which is a compound exhibiting temperature and alkali stability, preferably an aromatic or aliphatic low molecular weight compound, which is inert under the conditions of use.
[0039] In the case of structural units according to the general formulae V to VIII, the anion-exchange groups C are three-dimensionally chemically connected (i.e. cross-linked) to one another via bridges V, where essentially at each end of the polymer chain, and possibly also in side groups, K is present in a linked state as an end group Z, which is a compound exhibiting temperature and alkali stability, preferably an aromatic or aliphatic low molecular weight compound that is inert under the conditions of use.
[0040] According to the invention, in the case of the structural units according to the general formulae V to VIII, at least one K is a bond X, which is connected to a water-insoluble polymer B, which is preferably aromatic or aliphatic and inert under the conditions of use, and at the same time, at least one K represents an end group Z, which is present free from connection to a water-insoluble polymer B, which is preferably aromatic or aliphatic and inert under the conditions of use.
[0041] Advantageously, more K are bond sites X that are connected to the water-insoluble polymer B, which is preferably aromatic or aliphatic and inert under the conditions of use, than are bond sites X that are not connected to the water-insoluble polymer B, which is preferably aromatic or aliphatic and inert under the conditions of use. However, when K is a terminal group Z, it is not connected to the polymer B.
[0042] As terminal group Z there may advantageously be present an alkyl thioether, or an aryl thioether, or a benzyl thioether.
[0043] The linkage X may advantageously be an N,N-diallylpiperidinium ether, or an N,N-diallylpyrrolidinium ether, or an N,N-diallylaminoethyl ether, or a methacrylamide ethyl ether, or a methacrylic acid ester, or a methacrylic acid hydroxypropyl ether, or a xylylene ether, or a phenylene sulfone ether.
[0044] In the case of the bonds X, one or more or all of the bonds X are linked to their respective counterparts by a covalent chemical bond. Advantageously, the majority of the bonds X are linked to their respective counterparts by a covalent chemical bond.
[0045] In the anion exchanger material according to the present invention, the bond between the anion exchange group C and the water-insoluble polymer B according to the general formulae I to VIII can also be effected by ionic bonding between the anion exchange group C and the acidic group of the polymer B.
[0046] The bridge V is preferably selected from the group consisting of tetraallyl ammonium chloride, tetraalkylallyl ammonium chloride, diallyl-dialkylallyl ammonium chloride, 1,4-divinylbenzene, divinyl sulfone, divinyl sulfide, divinyl sulfoxide, divinyl ether, diacrylamide, dimethacrylamide, N,N,N',N'-tetraallyl-4,4'-trimethylenedipiperidinium chloride, N,N,N',N'-tetraalkylallyl-4,4'-trimethylenedipiperidinium chloride, N,N-diallyl-N',N'-dialkylallyl-4,4'-trimethylenedipiperidinium chloride, aryl-N,N',N'-aryl-4,4'-trimethylenedipiperidinium chloride, N,N,N'-triallyl-N'-alkylallyl-trimethylenedipiperidinium chloride, N,N,N'-tetraallylpiperazinium chloride, N,N,N',N'-tetraalkylallylpiperazinium chloride, N,N-diallyl-N',N'-dialkylallylpiperazinium chloride, N-allyl-N,N',N'-trialkylallylpiperazinium chloride, or N,N,N'-triallyl-N'-alkylallylpiperazinium chloride. Instead of the above ammonium chloride, its bromide or iodide can also be used.
[0047] If D is absent and / or m=0, this means within the scope of the present invention that the cyclic structural element of the anion-exchange group C is a five-membered ring.
[0048] The water-insoluble polymer B, which advantageously also exhibits temperature and / or alkaline stability, is advantageously a polyethersulfone, or a polysulfone, or a polyphenylene, or a polyphenylene ether, or a polyphenylene sulfide, or a poly(perfluoroethylene propylene), or a polytetrafluoroethylene, or a poly(ethylene tetrafluoroethylene), or a perfluoroalkoxy polymer, or a polystyrene, or a polyethylene, or a polypropylene.
[0049] Comonomer A is also preferably styrene, and / or α-methylstyrene, and / or N-vinylcarbazole, and / or methacrylic esters, and / or N-vinylpyrrolidone, and / or N,N-diallylacrylamide, and / or N,N-diallylacrylsulfonamide, and / or diallyl ethers, and / or 1,2-diallylbenzene, and / or diallyl sulfides, and / or chlorotrifluoroethylene, and / or tetrafluoroethylene, and / or hexafluoropropylene, and / or 1,2-divinylbenzene.
[0050] Here, the comonomer A is advantageously present to spatially separate the charged groups.
[0051] Advantageously, R1 is nitrogen, R6 to R9 are hydrogen, R2 and / or R3 are hydrogen or a methyl group, and R4 and / or R5 are a methyl or ethyl group.
[0052] The water-insoluble anion exchange material according to the present invention is achieved in that the nitrogen- or phosphorus-containing anion exchange group C in the water-insoluble anion exchange material according to the present invention is incorporated into a cyclic (heterocyclic) or spirocyclic compound of a structural unit according to at least one of the general formulae I to VIII.
[0053] Furthermore, the hydrogen atom in the β position relative to the positively charged atom in the anion-exchange group C in the structural unit according to at least one of the general formulae I to VIII may be substituted with an alkyl or aryl group.
[0054] The water-insoluble anion exchanger material of the present invention is produced by incorporating the anion exchange group C into a structural unit according to at least one of the general formulae I to VIII as a segment in a linear block copolymer (which also has a brushlike morphology due to polymerized side chains) or by preparing a three-dimensionally crosslinked polymer from the anion exchanger C and creating an end group Z (K=Z in formulae V to VIII) and connecting it to the water-insoluble polymer B via a bond X (K=X in formulae V to VIII).
[0055] Improving the alkaline and temperature stability of water-insoluble materials according to the present invention allows for the development of new application areas or improved efficiency in known applications.
[0056] The water-insoluble anion exchanger materials according to the invention can be used for anion exchange membranes or so-called anion exchange resins, where the anion exchange membranes consist essentially and at least to a large extent of linear anion exchange groups C which are constituents of structural units according to at least one of the general formulae I to IV, and the anion exchange resins consist essentially and at least to a large extent of cross-linked anion exchange groups C which are constituents of structural units according to at least one of the general formulae V to VIII.
[0057] A further advantageous property of the water-insoluble anion exchange material according to the invention is its odorlessness.
[0058] The water-insoluble anion exchange material according to the present invention is prepared by cyclopolymerization.
[0059] Advantageously, as monomers for preparing the anion-exchange groups C, N,N-diallyl compounds and / or N,N-dialkylallyl compounds and / or N-allyl-N-alkylallyl compounds of aliphatic or aromatic or cycloaliphatic secondary amines are used, such as, for example, diallyldimethylammonium chloride, diallylpiperidinium chloride, diallylpyrrolidinium chloride, allyl-methallyldimethylammonium chloride, allyl-methallylpiperidinium chloride, allyl-methallylpyrrolidinium chloride, dimethallyldimethylammonium chloride, dimethallylpiperidinium chloride, dimethylallylpyrrolidinium chloride, diallyl-3,4-dimethylpyrrolidinium chloride, diallyl-3,3,4,4-tetramethylpyrrolidinium chloride, diallyl-3,5-dimethylpiperidinium chloride, diallyl-3,3,5,5-tetramethylpiperidinium chloride, diallyl-diphenylammonium chloride. Likewise advantageously, P,P-diallyl compounds of aliphatic, aromatic or cycloaliphatic secondary phosphines and / or P,P-dialkylallyl compounds and / or P-allyl-P-alkylallyl compounds, such as diallyldimethylphosphonium chloride, diallyldiphenylphosphonium chloride, can be used as such monomers. Instead of ammonium chloride or phosphonium chloride, the corresponding bromides or iodides can also be used.
[0060] The water-insoluble anion exchanger material according to the present invention has a significantly higher temperature stability than comparable membrane materials according to the prior art, especially under alkaline conditions. This means that the anion exchanger material according to the present invention can be used without problems for such materials in existing application areas, thereby improving the efficiency of the process. The improved properties also make it possible to open up new application areas for the material according to the present invention.
[0061] In the following the invention will be explained in more detail by means of two examples. EXAMPLES
[0062] Example 1 An anion exchange membrane is prepared from a plurality of anion exchange groups C (with attachment via a water-insoluble polymer B) in a structural unit according to general formula II.
[0063] To prepare the anion exchange membrane, firstly the water-insoluble polymer B is prepared. For this purpose, 52 mmol of 4,4'-difluorodiphenylsulfone and 50 mmol of 4,4'-bis-trimethylsiloxydiphenylsulfone are dissolved in 50 ml of N-methylpyrrolidone (NMP), after which 75 mmol of potassium carbonate are added. The mixture is stirred at 175° C. for 16 hours under an argon atmosphere. The temperature is subsequently increased to 190° C. for 2 hours and another 100 mg of 4,4'-difluorodiphenylsulfone is added. After cooling, the reaction product is precipitated in 1000 ml of ethanol with the addition of 5 ml of 37% hydrochloric acid. The product is aspirated, washed with 250 ml of ethanol for 5 hours at 50° C., aspirated and dried in a vacuum at 100° C. The target product has a molecular weight Mn( 1 1H-NMR spectrum) and has no OH end groups. [ka]
[0064] To prepare the bond X in polymer B by the reaction shown below, 2 mmol of polyethersulfone and 4 mmol of 4-hydroxypiperidine are dissolved in 50 ml of NMP and 6 mmol of potassium carbonate are added. The starting solution is stirred for 16 hours at 175° C., and the intermediate product is subsequently precipitated with 500 ml of ethanol. The resulting polymer is stirred in ethanol for 5 hours at 50° C., filtered off and dried in vacuum at 100° C. [ka]
[0065] The target product is piperidine-terminated polyethersulfone. The yield is 90%. The complete reaction of the fluorine end groups with 4-hydroxypiperidine is 1 1H-NMR spectrum.
[0066] 0.5 mmol of this piperidine-terminated polyethersulfone is dissolved in 25 ml of dimethylsulfoxide (DMSO), 4 mmol of potassium carbonate is added and heated to 75° C. Over a period of 30 minutes, 4 mmol of allyl chloride (dissolved in 10 ml of DMSO) is added dropwise to the reaction mixture. After complete addition of the allyl chloride dissolved in DMSO, the mixture is stirred at 90° C. for 24 hours. After cooling, the polyethersulfone diallylpiperidinium-terminated by bond X is precipitated in ethanol, stirred in fresh ethanol at 50° C. and subsequently filtered off. The product is dried in vacuum at 50° C. The yield is 85%. The complete formation of the terminal quaternary ammonium salts is 1 Identification was performed using H-NMR spectrum. [ka]
[0067] Then, to prepare a compound having multiple anion exchange groups C according to the structural unit of general formula II, 0.1 mmol of diallylpiperidinium-terminated polyethersulfone (polymer B having linkage X) and 4 mmol of N,N-diallylpyrrolidinium chloride (anion exchange group C according to formula II, prepared according to the procedure according to Vynck et al., Macromol. Rapid Commun. 18, 1997, 149-156) are dissolved in 50 ml of DMSO and dissolved oxygen is removed by four freeze-thaw cycles. The reaction solution is heated to 90°C, 4 mol% AIBN is added, and the mixture is stirred at 90°C for 24 hours under an argon atmosphere. After cooling, the generated polyethersulfone-poly(azoniaspiro[4,4]nonane) block polymer is treated with thiophenol in the presence of a copper(I) salt to saturate the terminal double bonds, followed by precipitation in water. The homopolymer possibly generated during the reaction is removed by extraction with water in a Soxhlet extractor. 1 The composition determined by the H-NMR spectrum corresponds to the monomer composition according to formula II. The yield is 95%. [ka]
[0068] The polyethersulfone-poly(azoniaspiro[4,4]nonane) block polymer thus prepared is then used to prepare a membrane. For this purpose, 0.5 g of polyethersulfone-poly(azoniaspiro[4,4]nonane) block polymer is dissolved in 10 mL of N-methylpyrrolidone, filtered and transferred to a Petri dish with a diameter of 7 cm. The solvent N-methylpyrrolidone is removed in vacuum at room temperature for 2 h, then at 40 °C for 2 h, then at 60 °C for 2 h, and then at 100 °C for 24 h. The resulting membrane is peeled off from the Petri dish with water, washed in water at 70 °C for 4 h, and subsequently dried in vacuum at 50 °C until constant mass.
[0069] A membrane made from polyethersulfone-poly(azoniaspiro[4,4]nonane) block copolymer has a dry thickness of 70 μm, an ion exchange capacity of 1.30 mmol / g, a water absorption of 65% at 80 °C, and a hydroxide ion conductivity of 70 mS / cm at 80 °C and 95% relative humidity.
[0070] The membrane material polyethersulfone-poly(azoniaspiro[4,4]nonane) block copolymer is characterized with regard to its temperature stability. For this purpose, 0.5 g of membrane from polyethersulfone-poly(azoniaspiro[4,4]nonane) block copolymer is first stored in 2 M sodium hydroxide solution for 24 hours in order to transfer the anion exchanger material to the OH form. The membrane is then placed in 5 ml of 2 N sodium hydroxide solution and subjected to a melting test in a container, the contents of which are maintained at a temperature of 120 ° C for 168 hours. After cooling, the container is opened, the anion exchanger material is washed with water and subsequently stored in 1 M sodium chloride solution for 24 hours. The sample is again washed with water and dried at 50 ° C in a vacuum until the mass is constant.
[0071] In that case, the membrane material showed the following results, where these values were calculated before and after determining the temperature stability, respectively: mass Before test = 0.5g, after test = 0.49g Ion exchange capacity Before test = 1.30mmol / g, after test = 1.29mmol / g Hydroxide ion conductivity (80℃, 95% relative humidity) Before test = 70 mS / cm, after test = 69 mS / cm.
[0072] The difference in results is within the margin of error for each assay.
[0073] Example 2 An anion exchange membrane is prepared from a crosslinked compound having a plurality of anion exchange groups C (attached via a water-insoluble polymer B) which are constituents of a structural unit according to the general formula VI.
[0074] To prepare an anion exchange membrane, first a water-insoluble polymer B having K (representing a bond X) is prepared according to Example 1. A solution of 0.1 mmol of polymer B, 10 mmol of N,N-diallylpiperidinium chloride, and 2 mmol of N,N,N,N-tetraallylammonium chloride as crosslinking moiety V is dissolved in 10 mL of dimethylsulfoxide with 0.1 mmol of 2,4,6-trimethylbenzoyldiphenylphosphine oxide (DPO) as a UV initiator and thoroughly degassed. The solution is transferred to a Petri dish with a diameter of 7 cm covered with a quartz glass plate and irradiated with UV light (power 8 W) having a wavelength of 254 nm at room temperature for 10 minutes. The solvent is subsequently removed in vacuum at a temperature of 100-120 ° C. The anion exchanger material is washed with water and treated with thiophenol in the presence of a copper (I) salt in order to saturate the terminal double bonds. The anion exchange membrane is again thoroughly washed with water and dried in vacuum to constant weight. The membrane has a thickness (dry) of 100 μm, an ion exchange capacity of 3.35 mmol / g, a water absorption rate of 100% (at 80° C.), and a hydroxide ion conductivity of 90 mS / cm (at 80° C. and 95% relative humidity). [ka]
[0075] This membrane material is characterized by its temperature stability. For this purpose, 0.5 g of membrane is first stored in 2 M sodium hydroxide solution for 24 hours to transfer the anion exchanger material to the OH form. The membrane is then placed in 5 ml of 2 N sodium hydroxide solution and subjected to a melting test in a container, the contents of which are maintained at a temperature of 120° C. for 168 hours. After cooling, the container is opened, the anion exchanger material is washed with water and then stored in 1 M sodium chloride solution for 24 hours. The sample is again washed with water and dried at 50° C. in a vacuum until the mass is constant.
[0076] The membrane material then exhibited the following results, where these values were calculated before and after determining the temperature stability, respectively: mass Before test = 0.5g, after test = 0.49g Ion exchange capacity Before test = 3.35mmol / g, after test = 3.32mmol / g Hydroxide ion conductivity (80℃, 95% relative humidity) Before test = 90 mS / cm, after test = 88 mS / cm.
[0077] The difference in results is within the margin of error for each assay.
Claims
1. A water-insoluble anion exchanger material consisting of at least linearly polymerized and / or branched and / or crosslinked anion exchange groups C with one another, said anion exchange groups C being constituents of structural units according to at least one of the following general formulae V to VIII: 【Chemistry 1】 (In the formula, ・R 1 is nitrogen and / or phosphorus, ・R 2 ~R 9 is a substituent, R 2 and R 3 is hydrogen or at least one group R 2 and R 3 If is not hydrogen, R 2 and / or R 3 is an alkyl group or an aryl group, and R 4 and R 5 are each an alkyl group and / or an aryl group, and R 6 ~R 9 is hydrogen or at least one group R 6 ~R 9 is not hydrogen, these groups R 6 ~R 9 is an alkyl group or an aryl group, and C is an anion exchange group C, and V is a bridge moiety, and K is an end group or a bond, and D is absent or at least one methylene group, oxygen or sulfur, and if D is absent, the cyclic structural element of the anion exchange group C is a five-membered ring; and A is a component derived from a comonomer selected from the group consisting of styrene, α-methylstyrene, N-vinylcarbazole, methacrylic ester, N-vinylpyrrolidone, N,N-diallylacrylamide, N,N-diallylacrylsulfonamide, diallyl ether, 1,2-diallylbenzene, diallyl sulfide, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, and 1,2-divinylbenzene; and 2≦n≦100, and m=0 or 1, and 50 mol%≦x≦99 mol%, and y=(100 mol%−x), and 10 mol%≦w≦100 mol%, Where: The anion exchange groups C are crosslinked with each other via crosslinking moieties V as structural unit components of the general formulae V to VIII, and substantially all K as end groups are components derived from compounds exhibiting temperature stability and alkali stability, and all K as bonding moieties are bonded to water-insoluble polymers exhibiting temperature stability and alkali stability by chemical covalent bonds; and / or The bonding portion is a component derived from N,N-diallylpiperidinium ether, or N,N-diallylpyrrolidinium ether, or N,N-diallylaminoethyl ether, or methacrylamide ethyl ether, or methacrylic acid ester, or methacrylic acid hydroxypropyl ether, or xylylene ether, or phenylene ether sulfone, and a covalent bond is formed with the water-insoluble polymer via an ether bond or an ester bond on the one hand, and a chemical bond with the anion exchange group C is formed by reaction of at least one double bond capable of radical polymerization on the other hand; the terminal group is an alkyl thioether, an aryl thioether, or a benzyl thioether; The water-insoluble polymer exhibiting temperature and alkali stability is polyethersulfone, or polysulfone, or polythioethersulfone, or polyphenylene, or polyphenylene ether, or polyphenylene sulfide, or poly(perfluoroethylene propylene), or polytetrafluoroethylene, or poly(ethylene-tetrafluoroethylene), or perfluoroalkoxy polymer, or polystyrene, or polyethylene, or polypropylene, or a sulfonated and / or carboxylated and / or phosphonated polymer of the polyethersulfone, or polysulfone, or polyphenylene, or polyphenylene ether, or polyphenylene sulfide, or poly(perfluoroethylene propylene), or polytetrafluoroethylene, or poly(ethylene-tetrafluoroethylene), or perfluoroalkoxy polymer, or polystyrene, or polyethylene, or polypropylene class. The water-insoluble anion exchange material.
2. 2. The water-insoluble anion exchange material according to claim 1, wherein the anion exchange groups C according to formulae V-VIII are crosslinked via a crosslinking moiety V and K is a linking moiety to which a water-insoluble polymer exhibiting temperature and alkali stability is attached by a chemical covalent bond.
3. 2. The water-insoluble anion exchange material according to claim 1, wherein the bridge V is selected from the group consisting of tetraallyl ammonium, tetraalkylallyl ammonium, diallyl-dialkylallyl ammonium, N,N,N',N'-tetraallyl-4,4'-trimethylenedipiperidinium, N,N,N',N'-tetraalkylallyl-4,4'-trimethylenedipiperidinium, N,N-diallyl-,N',N'-dialkylallyl-4,4'-trimethylenedipiperidinium, N-allyl-N,N',N'-trialkylallyl-4,4'-trimethylenedipiperidinium, or N,N,N'-triallyl-N'-alkylallyl-4,4'-trimethylenedipiperidinium. the water-insoluble anion exchange material being a component derived from N,N,N',N'-tetraarylpiperazinium, or N,N,N',N'-tetraalkylarylpiperazinium, or N,N-diallyl-N',N'-dialkylarylpiperazinium, or N-allyl-N,N',N'-trialkylarylpiperazinium, or N,N,N'-triallyl-N'-alkylarylpiperazinium chloride and / or bromide and / or iodide, or 1,4-divinylbenzene, or divinyl sulfone, or divinyl sulfide, or divinyl sulfoxide, or divinyl ether, or diacrylamide, or dimethacrylamide.
4. 2. The water-insoluble anion exchange material according to claim 1, wherein as monomers for producing the anion exchange groups C, N,N-diallyl compounds and / or N,N-dialkylallyl compounds and / or N-allyl-N-alkylallyl compounds of aliphatic, aromatic or alicyclic secondary amines, P,P-diallyl compounds and / or P,P-dialkylallyl compounds and / or P-allyl-P-alkylallyl compounds of aliphatic, aromatic or alicyclic secondary phosphines, and / or chlorides and / or bromides and / or iodides of these compounds are used.
5. The water-insoluble anion exchange material according to claim 4, wherein diallyl dimethyl ammonium chloride, diallyl piperidinium chloride, diallyl pyrrolidinium chloride, allyl-methallyl dimethyl ammonium chloride, allyl-methallyl piperidinium chloride, allyl-methallyl pyrrolidinium chloride, dimethallyl dimethyl ammonium chloride, dimethallyl piperidinium chloride, dimethyl allyl pyrrolidinium chloride, diallyl-3,4-dimethyl pyrrolidinium chloride, diallyl-3,3,4,4-tetramethyl pyrrolidinium chloride, diallyl-3,5-dimethyl piperidinium chloride, diallyl-3,3,5,5-tetramethyl piperidinium chloride, diallyl-diphenyl ammonium chloride, diallyl dimethyl phosphonium chloride, or diallyl diphenyl phosphonium chloride is used as a monomer for producing the anion exchange group C.
6. 2. The water-insoluble anion exchange material according to claim 1, 1 is nitrogen.
7. 2. The water-insoluble anion exchange material according to claim 1, 2 and / or R 3 is a methyl group and / or hydrogen.
8. 2. The water-insoluble anion exchange material according to claim 1, 4 and R 5 wherein the water-insoluble anion exchange material is an alkyl group.
9. 2. The water-insoluble anion exchange material according to claim 1, 6 ~R 9 wherein R is hydrogen.
10. 2. The water-insoluble anion exchange material according to claim 1, wherein 10≦n≦50.
Citation Information
Patent Citations
Water-soluble anion exchanger materials
JP2017222839A